2020
DOI: 10.3390/agronomy10010134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Water Availability on Root Placement and Shoot Development in Landraces and Modern Barley Cultivars

Abstract: Early vigor has been proposed as a favorable trait for cereals grown in drought-prone environments. This research aimed at characterizing early stage shoot and root growth of three Spanish barley landraces compared with three modern cultivars. Genotypes were grown in an automated phenotyping platform, GrowScreen-Rhizo, under well-watered and drought conditions. Seminal and lateral root length, root system width and depth were recorded automatically during the experiment. Drought induced greater growth reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 71 publications
(83 reference statements)
3
10
0
Order By: Relevance
“…Reduction in agricultural productivity leads to shrinking revenue for local farmers. The loss of production substantially impacts farmers' livelihoods and economies [24]. Wheat (Triticum aestivum L.) crop is a major cereal crop and a common food source worldwide.…”
Section: Introduction Drought Stressmentioning
confidence: 99%
“…Reduction in agricultural productivity leads to shrinking revenue for local farmers. The loss of production substantially impacts farmers' livelihoods and economies [24]. Wheat (Triticum aestivum L.) crop is a major cereal crop and a common food source worldwide.…”
Section: Introduction Drought Stressmentioning
confidence: 99%
“…In general, drought had a greater effect on the above-ground than under-ground growth in potato crop [36,55], and in the case of other crops [59][60][61]. In vitro experiments with potatoes yielded similar results in osmotic stress-induced changes in shoots and root systems [32,34].…”
Section: Discussionmentioning
confidence: 76%
“…In accordance with these results, Kumar et al [21] reported that sugars and amino acids increased significantly in the aerial organs of different crops under drought stress. In addition, greater growth reduction was observed in shoots than in roots of barley plants subjected to drought [28].…”
Section: Resultsmentioning
confidence: 94%